SDTE: A Secure Blockchain-Based Data Trading Ecosystem - Dai, Weiqi; Dai, Chunkai; Choo, Kim-Kwang Raymond; Cui, Changze; Zou, Deiqing; Jin, Hai (IEEE transactions on information forensics and security, 2020)
Data, a key asset in our data-driven economy, has fueled the emergence of a new data trading industry. However, there are a number of limitations in conventional data trading platforms due to the existence of dishonest buyer/data broker. To mitigate these limitations, we posit the importance of a data processing-as-a-service model, which complements the conventional data hosting/exchange-as-a-service model. Specifically, in this paper, we introduce a secure data trading ecosystem and present a new blockchain-based data trading ecosystem (hereafter referred to as SDTE). In the ecosystem, both data broker and buyer are not able to obtain access to the seller's raw data, as they are only getting access to the analysis findings that they require. In other words, we reduce the challenge of securing the dataset to the challenge to secure the data processing. We also build a security model to analyze the data trading market and describe a new set of trading protocols for the entire data trading market. To demonstrate utility, we implement our proposed secure data trading platform (SDTP) on Ethereum & Intel's Software Guard Extensions (SGX) and perform an in-depth analysis.